2009
DOI: 10.1017/s0029665109990267
|View full text |Cite
|
Sign up to set email alerts
|

New insights into adipose tissue atrophy in cancer cachexia

Abstract: Profound loss of adipose and other tissues is a hallmark of cancer cachexia, a debilitating condition associated with increased morbidity and mortality. Fat loss cannot be attributable to reduced appetite alone as it precedes the onset of anorexia and is much more severe in experimental models of cachexia than in food restriction. Morphological examination has shown marked remodelling of adipose tissue in cancer cachexia. It is characterised by the tissue containing shrunken adipocytes with a major reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
67
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 79 publications
(109 reference statements)
7
67
0
6
Order By: Relevance
“…Involuntary weight loss, such as that present in cancer cachexia, causes a decrease in the size of adipocytes without changes in their number, resulting in adipose tissue atrophy (Bing & Trayhurn 2009). Bing et al (2006) showed that the epididymal adipose tissue (EAT) of cachectic mice contained shrunken adipocytes with dramatically reduced cell size that may have resulted from the down-regulation of key adipogenic and lipogenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Involuntary weight loss, such as that present in cancer cachexia, causes a decrease in the size of adipocytes without changes in their number, resulting in adipose tissue atrophy (Bing & Trayhurn 2009). Bing et al (2006) showed that the epididymal adipose tissue (EAT) of cachectic mice contained shrunken adipocytes with dramatically reduced cell size that may have resulted from the down-regulation of key adipogenic and lipogenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…31 However, the most studied property of ZAG is its involvement in lipid metabolism associated with adipose tissue atrophy in cachexia. 32 …”
Section: Introductionmentioning
confidence: 99%
“…The recombination of wing epithelium with leg (fibroblastic) mesenchyme resulted in the generation of scales instead of feathers (Dhouailly et al 1978). Thus, each of the components of the stroma described above is essential for proper tissue homeostasis, maintaining architecture, and, most importantly, physiologically appropriate functions (Kalluri and Zeisberg 2006;Tlsty and Coussens 2006;Bing and Trayhurn 2009). …”
mentioning
confidence: 99%
“…As we now know, alterations of each of these stromal cell types can contribute to the tumorigenic process through remodeling of the stroma (Karagiannis et al 2012) and widespread dysregulation of cell signaling and intercellular cross-talk (Kalluri and Zeisberg 2006;Tlsty and Coussens 2006;Bing and Trayhurn 2009;Ishii et al 2016). Similar to reports for the malignant epithelium, the malignant stroma exhibits expression profiles that provide prognostic information independent of epithelial biomarkers (Finak et al 2008;Ma et al 2009;Ostman and Augsten 2009;Sharma et al 2010).…”
mentioning
confidence: 99%